Dampak Poligami Tanpa Persetujuan Istri Terhadap Keharmonisan Rumah Tangga - Harahap, Tuti Alawiyah; Siregar, Syapar Alim (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The focus of this research is the implementation of polygamy without the consent of the first wife which greatly affects household harmony in Sibanggor Tonga Village, Puncak Sorik Marapi District, Mandailing Natal Regency, by raising two main problems, namely 1) what is the background for polygamy without the wife's consent in the village. Sibanggor Tonga ? 2) What is the impact of polygamy without the wife's consent on the harmony of households practicing polygamy in Sibanggor Tonga Village?. The purpose of this study is to find out what is behind the occurrence of polygamy without the wife's consent and how it affects their household harmony.The approach used in this research is a qualitative-descriptive approach, namely collecting data through interviews, observations and document studies. This research is qualitative, namely research conducted by collecting primary data and secondary data on phenomena that are currently happening directly. The primary data from this research are the village head, community leaders and families who practice polygamy. And the secondary data in this research are books, journals, theses, and other supporting sources.The conclusion obtained in this study is that polygamous marriages that occurred in Sibanggor Tonga Village were carried out due to an error in understanding the verse that allowed polygamy, in which the emphasis of polygamy was only seen in terms of its permissibility, without paying attention to the permissibility of what is contained in the verse, on the basis of their common understanding of how polygamy is actually permitted by Islamic law and the law, and on the basis of abuse, in fact polygamy that occurred in Sibanggor Tonga Village is only used as a way to fulfill lust without considering the rights of the wife and children. their children so that it greatly affects the harmony of their household.